2021
DOI: 10.1128/aem.01036-21
|View full text |Cite
|
Sign up to set email alerts
|

Recent Evolution and Genomic Profile of Salmonella enterica Serovar Heidelberg Isolates from Poultry Flocks in Brazil

Abstract: Salmonella enterica Heidelberg is a serovar isolated from poultry-producing regions around the World. In Brazil, S. Heidelberg has been frequently detected in poultry flocks, slaughterhouses and chicken. The goal of the present study was to assess the population structure, recent temporal evolution and some important genetic characteristics of S. Heidelberg isolated from Brazilian poultry farms. Phylogenetic analysis of 68 S . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…Consistent with observations obtained in our study, recent surveys strongly support that S. Heidelberg may originate from a common ancestor, which circulates and persists in the Brazilian poultry production chain since at least 2004 (Kipper et al, 2021). More importantly, these strains are also nested with strains isolated from several sources and countries around the world supporting the hypotheses of intercontinental spread, which demonstrate that probably the common ancestor underwent diversification through genetic changes over time (Supplementary Material).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with observations obtained in our study, recent surveys strongly support that S. Heidelberg may originate from a common ancestor, which circulates and persists in the Brazilian poultry production chain since at least 2004 (Kipper et al, 2021). More importantly, these strains are also nested with strains isolated from several sources and countries around the world supporting the hypotheses of intercontinental spread, which demonstrate that probably the common ancestor underwent diversification through genetic changes over time (Supplementary Material).…”
Section: Discussionsupporting
confidence: 91%
“…One of the most important risk factors surrounding foodborne illness is the international food trade that has been circumstantially accompanied by Salmonellae dispersal beyond borders. In this context, there is a global dispersal of multidrugresistant lineages of serovar S. Heidelberg, reaching various countries in North America (Andrysiak et al, 2008;Centers for Disease Control and Prevention, 2014;Public Health Agency of Canada, 2014;Deblais et al, 2018;Cox et al, 2021), South America (Kipper et al, 2021), Europe (Liakopoulos et al, 2016b;Campos et al, 2018), and Asia (Wu et al, 2013). Therefore, the simultaneous increase and extended protraction of S. Heidelberg in many parts of the world have favored their genetic acquisition of virulence and antimicrobial resistance (AMR) genes through horizontal gene transfer (HGT), which has ultimately led to one of the most pressing global concerns.…”
Section: Introductionmentioning
confidence: 99%
“…A study evaluating 930 WGS of different Salmonella serovars retrieved from the public database of the National Center for Biotechnology Information (NCBI) and published in the last four decades, demonstrated the prediction of the MDR phenotype in 58% (540/930) of the isolates, highlighting ciprofloxacin and nalidixic acid with the highest frequency rates [39]. Other recent reports have also demonstrated that MDR is frequent in Salmonella serovars Heidelberg and Minnesota isolated from broilers, layers, and poultry-derived food in Brazil [44,[49][50][51][52].…”
Section: Antimicrobial Resistancementioning
confidence: 96%
“…The prolonged use of antimicrobials has possibly increased Salmonella resistance to the most used classes in the poultry production chains [39,43,44]. Overall, 6 out of the 10 most frequently poultry-associated Salmonella serovars in the United States (Enteritidis, Montevideo, Schwarzengrund, Infantis, Thompson, and Mbandaka) have been demonstrated to be generally pan-susceptible or with resistance to few antimicrobials, whereas four (Heidelberg, Typhimurium, Kentucky, and Senftenberg) are more commonly reported as resistant to many of them [45].…”
Section: Antimicrobial Resistancementioning
confidence: 99%
See 1 more Smart Citation